2010
DOI: 10.1016/j.ejso.2010.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Dual PET/CT with 18F-DOPA and 18F-FDG in metastatic medullary thyroid carcinoma and rapidly increasing calcitonin levels: Comparison with conventional imaging

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. M A N U S C R I P T A C C E P T E D ACCEPTED MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
83
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 29 publications
(40 reference statements)
1
83
1
Order By: Relevance
“…These findings differ from Koopmans et al (8), who found 75% negative scans in patients with calcitonin concentrations of less than 500 pg/mL, and from that of Hoergerle et al (7), who found no MTC-positive 18 F-DOPA PET scans if the calcitonin level was less than 550 pg/mL. Further, Marzola et al found higher calcitonin concentrations in PET-positive than -negative patients but did not notice any difference between the tracers used ( 18 F-FDG or 18 F-DOPA) (31). The American Thyroid Association recently recommended additional imaging in MTC in patients with a postsurgical calcitonin level of 150 pg/mL or greater (32), and our results are in line with this result.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…These findings differ from Koopmans et al (8), who found 75% negative scans in patients with calcitonin concentrations of less than 500 pg/mL, and from that of Hoergerle et al (7), who found no MTC-positive 18 F-DOPA PET scans if the calcitonin level was less than 550 pg/mL. Further, Marzola et al found higher calcitonin concentrations in PET-positive than -negative patients but did not notice any difference between the tracers used ( 18 F-FDG or 18 F-DOPA) (31). The American Thyroid Association recently recommended additional imaging in MTC in patients with a postsurgical calcitonin level of 150 pg/mL or greater (32), and our results are in line with this result.…”
Section: Discussionmentioning
confidence: 63%
“…As demonstrated by Ahlström et al in 1995 with 11 Clabeled DOPA (21), 18 F-DOPA has been used in the diagnosis of carcinoids (22)(23)(24), pheochromocytomas (25,26), glomus tumors (27), and pancreatic neuroendocrine tumors (28). Only a few studies have evaluated the value of 18 F-DOPA PET in MTC (7,8,29) and even fewer have used integrated 18 F-DOPA-PET/CT (9,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Calcitonin and carcinoembryonic antigen (CEA) doubling times are currently the most reliable markers for progression, but for accurate determination, serial measurements, which need time, are required. We compared 18 F-FDG PET and 18 F-dihydroxyphenylanaline ( 18 F-DOPA) PET with biochemical parameters and survival to assess whether these imaging modalities could be of value in detecting progressive disease. Methods: We evaluated the outcome of 18 F-FDG PET or 18 F-DOPA PET with calcitonin and CEA doubling times in 47 MTC patients.…”
mentioning
confidence: 99%
“…Among the functional imaging modalities, the superiority of FDOPA PET (Fig. 2) has been shown by several studies with a sensitivity ranging from 44% to 90% [26][27][28][29][30][31][32]. The results of these studies have also been confirmed in the preclinical setting: FDOPA small-animal PET was also found to be accurate for monitoring disease progression over time [33].…”
mentioning
confidence: 77%
“…For determination of a surveillance strategy for both sporadic and hereditary MTC, we now have the toolset to characterize tumours. Genetic testing, histological differentiation and grade (Ki-67 indices) [31], tumour secretogogues, and Ct and CEA levels and doubling times [1,9] can be used to develop a phenotype model to tailor individualized treatment and imaging surveillance. Customized imaging approaches will determine which radiopharmaceutical (FDG or non-FDG, especially FDOPA) is optimal for PET imaging of a given patient with MTC.…”
mentioning
confidence: 99%